Failure Mechanism Analysis of 253MA Vortex Finder in A CFB Boiler Under High-Temperature Erosion and Refractory Deposit Exposure - Martua Haposan Echo Sihite; Kusmono Kusmono (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: Circulating fluidized bed (CFB) boilers are widely applied in coal-fired power plants due to their fuel flexibility and low emissions. The vortex finder, a key cyclone component, separates solid particles from flue gas and is prone to wear under high-temperature, erosive conditions. Objective: This study aims to identify failure characteristics, analyze the causes, and explain the failure mechanism of a 253MA vortex finder in a 2 × 100 MW CFB boiler at PLTU Sebalang after 6,548 operating hours at 850–950°C. Methods: A multi-method approach was employed, including visual inspection, positive material identification (PMI), tensile testing, microhardness testing, optical microscopy, scanning electron microscopy with energy-dispersive spectroscopy (SEM-EDS), and X-ray diffraction (XRD) analysis to assess mechanical and microstructural degradation. Results: The vortex finder exhibited plastic deformation, material thinning, and deposition of foreign refractory material. Tensile strength decreased from 723.89 MPa to 677.84 MPa (6.36%), elongation decreased from 58% to 53%, and hardness decreased from 218.84 HV to 210.21 HV. Microstructural changes included grain coarsening and carbide precipitation, while SEM-EDS revealed surface roughening, early microcrack initiation, and compositional changes indicative of high-temperature oxidation. XRD confirmed that the deposits consisted of alumina–silica refractory material. Conclusion: Failure resulted from a synergistic mechanism involving high-velocity particle erosion, refractory deposit accumulation, and progressive microstructural degradation. Crack initiation and propagation ultimately led to structural failure. Recommendations include implementing erosion control measures, maintaining refractory linings, applying more erosion-resistant coatings or alternative materials, and adopting condition-based inspection strategies to enhance component reliability.